Endoscopic ultrasound-assisted cholecystogastrostomy by a novel fully covered metal stent for the treatment of gallbladder stones - Ge, Nan (Endosc Ultrasound, 2015)
An 85-year-old male patient with common bile duct stones and gallbladder stone was admitted to the hospital. Endoscopic ultrasound (EUS)-guided cholecystogastrostomy and the placement of a novel covered mental stent was performed after the endoscopic sphincter ectomy procedure. Two weeks later the stents were removed, and an endoscope was advanced into the gallbladder via the fistula, and cholecystolithotomy was performed. For weeks later gallbladder was assessed by abdominal ultrasound. EUS-guided cholecystogastrostomy with mental stent deployment was successfully performed. Two weeks after the procedure, the fistulas had formed, and the stent were removed. Endoscopic cholecystolithotomy was successfully performed through the fistula. The ultrasound exam of gallbladder 4 weeks later showed no stone remain and satisfactory function. The EUS-guided placement of a novel metal stent was a safe and simple approach to performing an endoscopic cholecystogastrostomy, which can subsequently allow procedures for treating biliary disease, including cholecystolithotomy.